Urban Policy in The Context of Socio-Economic Problems Arising From Global Crisis - Sikora-Fernandez, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
A crisis of a city is typically regarded as synonymous to the crisis of public finance – it arises from insufficient investments by the local and national public sector. However, contemporary cities face also other challenges, apart from the obvious lack of financial resources – such as effects of the global crisis which are cause predominantly by the actions of the private sector. The problems of contemporary cities require that public authorities professionalize in their approach to management. Sustainable, long-term development of a city will not be possible, unless many issues such as: communication, housing, water supply, waste management, rational management of space, modernization of various forms of development, education, health care, preventing social pathologies, proper social relations, shaping social structures or stimulating the development of income-generating functions are efficiently solved. That is why creating an adequate urban policy and implementing it with the use of appropriate methods and instruments which allow for efficient regulation of social relations and public service provision should be the domain of public authorities.